Desirable airfoil features for smaller-capacity straight-bladed VAWT - Islam, Mazharul; Ting, David S-K.; Fartaj, Amir (SAGE Publications, 2007)
In the small scale wind turbine market, the simple straight-bladed Darriues types vertical axis wind turbine (SB-VAWT) is very attractive for its simple blade design. A detailed aerodynamic performance analysis of the main aerodynamic challenges of this type of wind turbine were first discussed and subsequently the authors conducted further literature survey and computational analysis to shortlist aerodynamic characteristics of a desirable airfoil for a self-starting and better performing SB-VAWT. The required geometric features of the desirable airfoil to achieve the short listed characteristics were also discussed. It has been found out that conventionally used NACA symmetric airfoils are not suitable for smaller capacity SB-VAWT. Rather, it is advantageous to utilize a high-lift and low-drag asymmetric thick airfoil suitable for low speed operation typically encountered by SB-VAWT.